Nasionalisme Etnis Tionghoa: Faktor-Faktor Penyebab Etnis Tionghoa Memiliki Rasa Nasionalisme yang Lemah terhadap Negara Malaysia - Gianturi, Egi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
The Chinese or Chinese ethnic group in Malaysia is very different from the Chinese ethnic group in Indonesia, this can be seen from the perspective of language use, both the national language and also everyday language. The biggest problem for ethnic Chinese in Malaysia is that ethnic Chinese cannot or cannot pronounce Malay which is the official national language, not only that, there is segregation, especially segregation in the field of education. Education in Malaysia is separated based on ethnicity in Malaysia. The political system that exists in Malaysia is very different from the political system understood by ethnic Chinese, leaning more towards communism. With these differences, ethnic Chinese in Malaysia have boundaries with ethnic Malays, making them feel a very weak sense of love (nationalism) towards Malaysia. This research is based on political theory. This political role is what gives direction or outlook to the Chinese ethnic group in Malaysia, with this difference making the Chinese prefer to maintain their original identity rather than assimilate into tennis in Malaysia. The research method used refers to historical research methods with a descriptive qualitative approach and literature. The weak sense of nationalism of ethnic Chinese towards Malaysia is caused by several things such as lack of assimilation and assimilation with other ethnicities, educational separation, differences in political sects, different social status and discrimination, sensitive religious issues.